# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = 2 y-2 x^{2}-3
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 x -y
\] |
✓ |
✓ |
|
\[
{}1+y^{2}+\left (x^{2}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+y^{2}+x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime }-y \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}1+y^{2} = x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x \sqrt {1+y^{2}}+y y^{\prime } \sqrt {x^{2}+1} = 0
\] |
✓ |
✓ |
|
\[
{}x \sqrt {1-y^{2}}+y \sqrt {-x^{2}+1}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{-y} y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y \ln \left (y\right )+x y^{\prime } = 1
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = a^{x +y}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y} \left (x^{2}+1\right ) y^{\prime }-2 x \left (1+{\mathrm e}^{y}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 x \sqrt {1-y^{2}} = \left (x^{2}+1\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x} \sin \left (y\right )^{3}+\left (1+{\mathrm e}^{2 x}\right ) \cos \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} \sin \left (x \right )+\cos \left (x \right )^{2} \ln \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x -y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x +b y+c
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right )^{2} y^{\prime } = a^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = a \left (x y+1\right )
\] |
✓ |
✓ |
|
\[
{}a^{2}+y^{2}+2 x \sqrt {a x -x^{2}}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}\cos \left (y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y^{\prime }} = 1
\] |
✓ |
✓ |
|
\[
{}\sin \left (y^{\prime }\right ) = x
\] |
✓ |
✓ |
|
\[
{}\ln \left (y^{\prime }\right ) = x
\] |
✓ |
✓ |
|
\[
{}\tan \left (y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y^{\prime }} = x
\] |
✓ |
✓ |
|
\[
{}\tan \left (y^{\prime }\right ) = x
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } \cos \left (y\right )+1 = 0
\] |
✗ |
✓ |
|
\[
{}x^{2} y^{\prime }+\cos \left (2 y\right ) = 1
\] |
✗ |
✓ |
|
\[
{}x^{3} y^{\prime }-\sin \left (y\right ) = 1
\] |
✗ |
✗ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }-\frac {\cos \left (2 y\right )^{2}}{2} = 0
\] |
✗ |
✓ |
|
\[
{}{\mathrm e}^{y} = {\mathrm e}^{4 y} y^{\prime }+1
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime } = y-1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x \left (\pi +y\right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+\sin \left (2 y\right ) = 1
\] |
✗ |
✓ |
|
\[
{}x y^{\prime } = y+x \cos \left (\frac {y}{x}\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x -y+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y \left (\ln \left (y\right )-\ln \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y^{2}-x y+x^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+\sqrt {y^{2}-x^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}4 x -3 y+\left (2 y-3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y-x +\left (x +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y-2+\left (1-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 y-7 x +7-\left (3 x -7 y-3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y-2+\left (x -y+4\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y+\left (x -y-2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +3 y-5+\left (3 x +2 y-5\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}8 x +4 y+1+\left (4 x +2 y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x -2 y-1+\left (3 x -6 y+2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y+\left (x +y-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime } \left (x -y^{2}\right )+y^{3} = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{6}+x^{3} = 6 x y^{5} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y \left (1+\sqrt {x^{2} y^{4}+1}\right )+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y^{3}+3 \left (y^{3}-x \right ) y^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}x^{2}-x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = 2 x \,{\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = {\mathrm e}^{-x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \cos \left (x \right )-y \sin \left (x \right ) = 2 x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-2 y = x^{3} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \tan \left (x \right ) = \frac {1}{\cos \left (x \right )^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } x \ln \left (x \right )-y = 3 x^{3} \ln \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}\left (2 x -y^{2}\right ) y^{\prime } = 2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{2 y \ln \left (y\right )+y-x}
\] |
✓ |
✓ |
|
\[
{}\left (\frac {{\mathrm e}^{-y^{2}}}{2}-x y\right ) y^{\prime }-1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \,{\mathrm e}^{x} = 2 x \,{\mathrm e}^{{\mathrm e}^{x}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y \,{\mathrm e}^{x} = {\mathrm e}^{\left (1-x \right ) {\mathrm e}^{x}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \ln \left (2\right ) = 2^{\sin \left (x \right )} \left (-1+\cos \left (x \right )\right ) \ln \left (2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = -2 \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime }-y \cos \left (x \right ) = -\frac {\sin \left (x \right )^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } \cos \left (\frac {1}{x}\right )-y \sin \left (\frac {1}{x}\right ) = -1
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }-y = 1-\frac {2}{\sqrt {x}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+y = \left (x^{2}+1\right ) {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = 2 x
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime }+y \cos \left (x \right ) = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \cos \left (x \right )-y \sin \left (x \right ) = -\sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = 2 x y^{2}
\] |
✓ |
✓ |
|
\[
{}3 y^{2} y^{\prime } x -2 y^{3} = x^{3}
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+{\mathrm e}^{y}\right ) y^{\prime } = 3 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 x y = y \,{\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y \,{\mathrm e}^{x} = 2 \sqrt {y \,{\mathrm e}^{x}}
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime } \ln \left (x \right )+\frac {y}{x} = \frac {\cos \left (x \right )}{y}
\] |
✓ |
✓ |
|
\[
{}2 \sin \left (x \right ) y^{\prime }+y \cos \left (x \right ) = y^{3} \sin \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}+1\right ) y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \cos \left (x \right ) = y^{2} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\tan \left (y\right ) = \frac {{\mathrm e}^{x}}{\cos \left (y\right )}
\] |
✓ |
✗ |
|
\[
{}y^{\prime } = y \left ({\mathrm e}^{x}+\ln \left (y\right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \cos \left (y\right )+\sin \left (y\right ) = 1+x
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }+1 = \left (x -1\right ) {\mathrm e}^{-\frac {y^{2}}{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x \sin \left (2 y\right ) = 2 x \,{\mathrm e}^{-x^{2}} \cos \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x \left (2 x^{2}+y^{2}\right )+y \left (2 y^{2}+x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2}+6 x y^{2}+\left (6 x^{2} y+4 y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x}{\sqrt {x^{2}+y^{2}}}+\frac {1}{x}+\frac {1}{y}+\left (\frac {y}{\sqrt {x^{2}+y^{2}}}+\frac {1}{y}-\frac {x}{y^{2}}\right ) y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}3 x^{2} \tan \left (y\right )-\frac {2 y^{3}}{x^{3}}+\left (x^{3} \sec \left (y\right )^{2}+4 y^{3}+\frac {3 y^{2}}{x^{2}}\right ) y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}2 x +\frac {x^{2}+y^{2}}{x^{2} y} = \frac {\left (x^{2}+y^{2}\right ) y^{\prime }}{x y^{2}}
\] |
✓ |
✓ |
|
\[
{}\frac {\sin \left (2 x \right )}{y}+x +\left (y-\frac {\sin \left (x \right )^{2}}{y^{2}}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2}-2 x -y+\left (2 y-x +3 y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|